Emerging insights into inflammatory bowel disease from the intestinal microbiota perspective: a bibliometric analysis - Zhang, Anqi; Wang, Fang; Li, Delong; Wang, Chong-Zhi; Yao, Haiqiang; Wan, Jin-Yi; Yuan, Chun-Su (Frontiers in Immunology, 2023)
Inflammatory bowel disease (IBD) has caused severe health concerns worldwide. Studies on gut microbiota have provided new targets for the prevention and treatment of IBD. Therefore, it is essential to have a comprehensive understanding of the current status and evolution of gut microbiota and IBD studies. A bibliometric analysis was performed on documents during 2003-2022 retrieved from the Scopus database, including bibliographical profiles, citation patterns, and collaboration details. Software programs of VOSviewer, CiteSpace, and the Bibliometrix R package visually displayed the mass data presented in the scientific landscapes and networks. A number of 10479 publications were retrieved, showing a steadily growing tendency in interest. Xavier Ramnik J. group led the total number of publications (73 papers) and 19787 citations, whose productive work aroused widespread concern. Among the 1977 academic journals, the most prolific ones were Inflammatory Bowel Diseases, Frontiers in Immunology, and Nutrients.Research outputs from the United States (US, 9196 publications), China (5587), and Italy (2305) were highly ranked. Our bibliometric study revealed that the role of gut microbiota has become a hot topic of IBD research throughout the world. These findings are expected to improve understanding of research characteristics and to guide future directions in this field.